The effective use of educational software and media in teaching and education - Kokaj, Agon; Kurshumlia, Mimoza; Hoxha, Ilmi (Edelweiss Applied Science and Technology, 2025)
The use of software tools for manipulating data and engineering mathematical models has made life much easier for us. Different software programs have allowed us to analyze 3D modeling to demonstrate concepts to students during various teaching sessions. Various software techniques have been developed that are not only efficient but also easy to manipulate. The use of software tools to calculate complex mathematical formulas and equations has been implemented and is being taught at universities worldwide, enabling students to better understand the material in a practical context. Similarly, software programs in music production have transformed the process of creating and teaching compositions, allowing students to experiment with sound design and digital instruments in real-time. This approach deepens their understanding of musical theory and composition. The use of software in teaching is an ongoing process, especially with the advent of AI and ICT, which continue to advance educational methods and tools.